Reliability and variation in mitochondrial respiration in human adipose tissue. (1st January 2021) - Sahl, Ronni Eg; Høy Helms, Eva Frederikke; Schmücker, Malte; Flensted-Jensen, Mathias; Ingersen, Arthur; Morville, Thomas; Dela, Flemming; Helge, Jørn Wulff; Larsen, Steen
ABSTRACT: Adipose tissue mitochondrial function is gaining increasing interest since it is a good marker of overall health. Methodological challenges and variability in assessing mitochondrial respiration in fresh adipose tissue with high-resolution respirometry are unknown and should be explored. Mitochondrial respiratory capacity (MRC) in human adipose tissue declines in a gradual manner when analyses are postponed 3 h and 24 h, with a statistically significant decline 24 h after obtaining the biopsy. This decline in MRC is associated with a reduced integrity of the outer mitochondrial membrane at both time points. This study suggests that the optimal amount of tissue to be used is 20 mg and that different technicians handling the biopsy do not affect MRC.